2023
DOI: 10.1186/s12884-023-05492-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health facility delivery among young mothers aged 15 – 24 years in Nigeria: a multilevel analysis of the 2018 Nigeria demographic and health survey

Abstract: Background Young mothers aged 15 to 24 years are particularly at higher risk of adverse health outcomes during childbirth. Delivery in health facilities by skilled birth attendants can help reduce this risk and lower maternal and perinatal morbidity and mortality. This study assessed the determinants of health facility delivery among young Nigerian women. Methods A nationally representative population data extracted from the 2018 Nigeria Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
1
0
0
Order By: Relevance
“…It was found that women who had at least an ANC visit were more likely to utilize health facilities during delivery. The finding is in line with previous studies conducted in Asia [ 44 , 52 ], Eastern Africa [ 34 , 58 ], and SSA [ 24 , 27 , 59 ]. The reason could be that during ANC visits, women are most likely to be informed about the benefits associated with health facility delivery [ 43 , 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was found that women who had at least an ANC visit were more likely to utilize health facilities during delivery. The finding is in line with previous studies conducted in Asia [ 44 , 52 ], Eastern Africa [ 34 , 58 ], and SSA [ 24 , 27 , 59 ]. The reason could be that during ANC visits, women are most likely to be informed about the benefits associated with health facility delivery [ 43 , 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, these alternative models reject the unitary model which assumes that household's preferences are identical, leading to the conclusion that some sort of bargaining process exists within the household. Based on such a conclusion, several authors established the effect of women's decision-making power at home on the utilisation of several maternal health care services including skilled birth attendance (Yaya et al, 2021;Dickson et al, 2021), antenatal and postnatal care (Annan et al, 2021;Sado et al, 2014) and delivery in a health facility (Ahmmed, 2022;Ilesanmi et al, 2023;Fikre and Demissie, 2012;Mokam and Zamo, 2022;Olubodun et al, 2023;Speizer et al, 2014;Sserwanja et al, 2023;Tiruneh et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To our knowledge, only Mokam and Zamo Akono (2022) have conducted such study in that context. Besides, there is not a consensus in the literature as there are some studies concluding either to a negative effect (Fikre and Demissie, 2012) or an insignificant effect (Olubodun et al, 2023;Sserwanja et al, 2023) of women's empowerment on health facility delivery. All in all, there is certainly a scope for more research on the effect of women's empowerment on health facility utilisation during childbirth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations